WOMEN OPPRESION IN SLEEPING WITH THE ENEMY MOVIE: A LIBERAL FEMINISM APPROACH - Febrianti , Intan (2007)
The major problem of this study is how oppression in Laura Burney is reflected in Sleeping with the Enemy movie based on liberal feminist approach. This study is to analyze structural elements of Sleeping with the Enemy movie and Laura's struggle to get freedom based on liberal feminist point of view This research paper is qualitative research. The object of the study is Sleeping with the Enemy movie directed by Joseph Ruben publish in 1991 by Twentieth Century Fox. The primary data source is the Sleeping with the Enemy movie it self and the secondary data sources are the other sources related to the analysis such as books of feminism, especially liberal feminism. The method of data collection is documentation research. The technique of data analysis is descriptive analysis. The result of the study shows the relationship between the movie and the social phenomena in America. In Sleeping with the Enemy movie, Joseph Ruben describes women's oppression in the early of twenty century as a way to describe women condition in America strongly dominant in subordinate place. The movie also views women must be brave to face the risk, in order to reach their right. Therefore, women should have brave mentality to support their purposes toward freedom. Furthermore, Joseph Ruben wants to say that women must have effort to rebel oppressive condition in the issues of women's position, role, rights, and participation.